Effects of pH on the microarchitecture of carbonate apatite granules fabricated through a dissolution–precipitation reaction - Wang, Zhibin; Shimabukuro, Masaya; Kishida, Ryo; Yokoi, Taishi; Kawashita, Masakazu (Frontiers in Bioengineering and Biotechnology, 2024)
Both the composition and architecture of artificial bone govern bone regeneration. Herein, carbonate apatite (CAp), which has a similar mineral composition to bone, was prepared by immersing calcium carbonate (CaCO3) in a phosphate solution with varying acidification levels (pH 6.0) to pH 8.9, to reveal the influence of pH on the composition and architecture of the resultant CAp granules. The composition, crystal morphology, and architecture of resultant CAp granules was well-characterized by X-ray diffraction, scanning electron microscopy, mercury intrusion porosimetry and so on. Consequently, the rate of compositional transformation from CaCO3 to CAp was much higher at pH 6.0 and pH 7.0 than pH 8.0 and pH 8.9. The pH of the phosphate solution did not affect the macroarchitecture of the resultant CAp granules. In contrast, the composition, crystal morphology, microarchitecture, and degradation behavior of the resultant CAp granules were affected by pH of the phosphate solution. In particular, the open-pore distributions and volumes of the CAp granules prepared at pH 6.0-8.9 were changed to reflect the microarchitecture of the samples. Therefore, this study revealed that the pH-controlled elution precipitation reaction is useful for controlling the composition, crystal morphology, microarchitecture, and degradation behavior of the resultant CAp, while preserving its macroarchitecture. Our findings provide fundamental insights into the design of artificial bones for bone regeneration.